The potential of energy behaviours in a smart(er) grid: Policy implications from a Portuguese exploratory study - Lopes, Marta A.R. (2016)
The transition to smart grids is an on-going process that may both shape and be shaped by end-users' energy behavioural adaptations. This study explores current and potential energy behavioural adaptations in Portugal during the smart grid transition process. A web-based survey was made to a representative sample of a specific segment of Portuguese residential end-users. The survey evaluated current energy behaviours and hypothetical future behaviours in a dynamic pricing scenario. Results show this population segment has a positive predisposition towards smart technologies and demand shifting, but it is less likely to accept load control and switch to the liberalised energy market. Factors influencing the behavioural potential are mostly related with market regulation, households' practices and usage behaviours, interference with the private domain, information and technical aspects, and social values. To facilitate behavioural adaptations several strategies are recommended, such as improving the energy market regulation, assessing households' behaviours, prioritising actions already embedded in households daily routines, not interfering with their activities and ensure an override option, and improving energy services, trust and information provided to end-users. The conclusions of the present study are of utmost importance for the design of more effective demand response programmes and energy policies.